PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL, SPIRITUAL TERHADAP PEMAHAMAN AKUNTANSI - Dian Khaerani; R. Ery Wibowo Agung S (Universitas Muhammadiyah Semarang, 2013)
The purposes of this study are to and analyze the influence of intellectual, emotional and spiritual intelligence to the understanding of accounting either stimulantly or partially.This study focused on the influence of intellectual, emotional and spiritual intelligence to the understanding of accounting by using primary data obtained from the questionnaire. Population of the study was obtained from the accounting students at three different universities in Semarang namely UNIMUS Semarang, UNNES and UDINUS. Number of samples taken was 50 respondents.The type of data collected is primary data. Hypothesis testing result indicated that the intellectual, emotional, spiritual intelligence had possitive relationship with the understanding of accounting. This study was taken as one source of literature and reference. It can be concluded that intellectual, emotional and spiritual intelligence has a positive impact on the understanding of accounting at 21.346. The influnece of the three independent variables on understanding accounting can be seen from the score of adjusted coefficient of determination which is more than 50 percent; 0.55 or 55 percent.Keywords: Intellectual intelligence, emotional intelligence, spiritual intelligence, accounting understanding.